EVALUATION OF THE INTERACTION OF STEEL SLIT PANEL-FRAME - ahmad nazifi (Iranian Society of Structrual Engineering (ISSE), 2019)
All buildings need a system that resists the lateral forces such as wind and earthquake. Such systems are commonly known as Lateral Force Resisting (LFR) Systems. The steel slit shear wall system is a new LFR system intended for zones with high seismicity. One of the essential constituent of the steel slit shear wall system is the slit. The shear wall has columns with slits forming links in between them. In the presence of lateral forces, these links work as a series of small flexural members in parallel and behave in double curvature reaching yield at both ends. The most notable advantages of such a system are ductile behavior and high ability to dissipate energy. In this paper, numerical analysis using Abaqus is performed to evaluate the effect of moment inertia of beam on the behavior of steel slit shear wall. In order to verify the efficiency and accuracy of the employed finite element method, Cortes and Liu tests are conducted. After wall, twelve frame models with different beams are established. The hysteresis curves, energy dissipation capacity, initial stiffness, and ultimate strength of frames are compared and analyzed. It is observed that by increasing the moment of inertia, deformation and dissipated energy of slit steel shear wall with defined slit increase. It should be noted that, initial stiffness of steel slit shear wall with ordinary slit is higher.